Vagus Nerve Stimulator: A Breakthrough for Refractory Epilepsy in Pakistan - Gule Zehra; Afshan Salah Uddin; Fareeha Masood et al (ziauddin University, 2024)
Epilepsy is the fourth most common neurological illness around the world characterized by abnormal electrical activity in the brain manifesting itself as seizures.